Assessment of Elementary Teachers’ Stress Factors and Adaptive Coping Strategies - Bacamante, Ires; Sabud, Marilou (Journal of Interdisciplinary Perspectives, 2025)
This research aimed to assess teachers' stress factors and coping mechanisms in central elementary schools for the school year 2023-2024. Findings revealed moderate stress among teachers in central schools in terms of the following indicator variables of pupils' behavior, teachers’ workload, time resources, interpersonal relationships, recognition, and well-being was moderate, which means that the teachers sometimes manifested the level of stress. The Pearson Product-Moment Correlation Coefficient indicated a significant relationship between teachers’ stress levels and their adaptive coping strategies. Most teachers are females, aged 36 to 45 years old, married, with a Teacher III designation, and handle many pupils in the classroom. The stress level among teachers in central schools regarding pupils’ behavior and teachers’ workload is high. Still, it is moderated regarding time resources, interpersonal relationships, recognition, and well-being. Central school teachers utilized coping strategies to cope with the stresses they encountered. It was recommended that the school heads in the Digos City Division provide technical assistance on enhancing stress resiliency in every teaching-learning process as they relate to the manifestations of the new strategies and pedagogical techniques of teaching. The central school teachers may teach co-teachers how to implement the pedagogical method in the workplace while reducing stress and developing adaptive coping strategies. Individual schools may continue to prioritize the mental health of every teacher. In addition, stress information advocacy workshops may be included in the priority improvement areas as they are included in the School Improvement Plan.